Noncompaction cardiomyopathy: sinus node disease as an initial manifestation treated with bicameral pacemaker - Carlesso, Vinícius Batista; Falsoni, Manoela; Pinto de Oliveira, Fredric Assis; Maurício, Vitória Adelaide de Sousa; Pachón Mateos, Juan Carlos (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
Noncompaction cardiomyopathy is a congenital disease that results from myocardial compaction failure in embryonic life. In this process there is the persistence of deep trabeculations and recesses that communicate with the ventricular cavity, resulting in myocardial thickening in two distinct layers. The clinical aspect of this disease in both children and adults is very heterogeneous, ranging from absence of symptomatology to a triad including congestive heart failure, arrhythmias and systemic thromboembolism. However, symptomatic bradycardias are very rare. We report the case of a patient with sinus node disease as the initial manifestation of non-compaction cardiomyopathy.